PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIME GAMES TOURNAMENT BERBASIS ONLINE DIMASA PANDEMI COVID 19 UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Yanti Listiana; Galih Dani Septiyan Rahayu (IKIP Siliwangi, 2021)
The success of teachers in conducting online learning in the Covid-19 pandemic situation depends on the ability of teachers to innovate in designing and concocting materials, learning methods, and what applications are in accordance with the materials and methods. Creativity is the key to success for a teacher to be able to motivate students to stay enthusiastic about learning online (online). The Time Games Tournament TGT learning model is a model that can be applied in online learning to eliminate children's boredom and provide learning variations. In this study, the research targets were the fourth-grade students of SDN 037 Sabang Bandung City, West Java Province, totaling 20 people. The material that becomes the focus of the research is the